DESENVOLVIMENTO CORPORAL E PARÂMETROS FISIOLÓGICOS DE NOVILHAS NELORE E CRUZADAS - SANTOS, Camylla Silveira; CASTRO, Micheline Feitosa; ALMEIDA, Gabrielly Benevides; SILVA, Milena Vitória; SANTOS, Aylpy Renan Dutra; OLIVEIRA, Dalton Mendes (ANAIS DO ENIC, 2025)
-